2015
DOI: 10.1038/jid.2015.94
|View full text |Cite
|
Sign up to set email alerts
|

Fidgetin-Like 2: A Microtubule-Based Regulator of Wound Healing

Abstract: Wound healing is a complex process driven largely by the migration of a variety of distinct cell types from the wound margin into the wound zone. In this study, we identify the previously uncharacterized microtubule-severing enzyme, Fidgetin-like 2 (FL2), as a fundamental regulator of cell migration that can be targeted in vivo using nanoparticle-encapsulated siRNA to promote wound closure and regeneration. In vitro, depletion of FL2 from mammalian tissue culture cells results in a more than two-fold increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 43 publications
1
71
2
Order By: Relevance
“…Furthermore, a recent study has shown that inhibition of the microtubule-severing protein fidgetinlike protein 2 (FIGNL2) promotes epidermal cell migration in vivo (Charafeddine et al, 2015), suggesting that the members of this protein family have important roles in 3D cell migration.…”
Section: Microtubule-associated Proteins In 3d Cell Migrationspecificmentioning
confidence: 99%
“…Furthermore, a recent study has shown that inhibition of the microtubule-severing protein fidgetinlike protein 2 (FIGNL2) promotes epidermal cell migration in vivo (Charafeddine et al, 2015), suggesting that the members of this protein family have important roles in 3D cell migration.…”
Section: Microtubule-associated Proteins In 3d Cell Migrationspecificmentioning
confidence: 99%
“…12 This discovery stemmed from an siRNA screen that was used to find the human equivalent of katanin, the severing enzyme whose depletion enhances the rate of Drosophila cell migration. 55 We assumed that if we could harness the same activity in human cells, we would have a potentially viable therapeutic target for enhancing wound healing.…”
Section: Fl2 As Novel Therapeutic Target For Wound Healing: a Case Studymentioning
confidence: 99%
“…Delivering small interfering RNA (siRNA) or microRNA (miRNA) [17,18] to inhibit gene expression post-transcriptionally is a promising biomedical technology that has been investigated for many applications including cancer therapeutics [19][20][21][22][23], wound healing [24][25][26], and tissue regeneration [6][7][8][9][10][27][28][29][30][31][32]. For example, RNAs have been used in tissue regeneration to induce the differentiation of human MSCs (hMSCs) [6][7][8][9][10], canine MSCs [30] and rat MSCs [31] into osteoblasts [6][7][8][9]30,31], chondrocytes [10] or adipocytes [7,8].…”
mentioning
confidence: 99%